2021
DOI: 10.3390/ijms22168449
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Releasing Drug Glyceryl Trinitrate Targets JAK2/STAT3 Signaling, Migration and Invasion of Triple-Negative Breast Cancer Cells

Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive disease with invasive and metastasizing properties associated with a poor prognosis. The STAT3 signaling pathway has shown a pivotal role in cancer cell migration, invasion, metastasis and drug resistance of TNBC cells. IL-6 is a main upstream activator of the JAK2/STAT3 pathway. In the present study we examined the impact of the NO-donor glyceryl trinitrate (GTN) on the activation of the JAK2/STAT3 signaling pathway and subsequent migration, invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…SCF/c-Kit axis regulates the migration of colorectal cancer [ 31 ] and cervical cancer [ 20 ], but to our knowledge this is the first report showing that c-Kit mediates TNBC cell migration. It has been demonstrated that the PI3K/Akt [ 32 ] and JAK2/STAT3 [ 33 ] cascades are important regulators of TNBC cell migration. Correspondingly, we observed that SCF stimulation induced the activation of Akt and STAT3 in migrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…SCF/c-Kit axis regulates the migration of colorectal cancer [ 31 ] and cervical cancer [ 20 ], but to our knowledge this is the first report showing that c-Kit mediates TNBC cell migration. It has been demonstrated that the PI3K/Akt [ 32 ] and JAK2/STAT3 [ 33 ] cascades are important regulators of TNBC cell migration. Correspondingly, we observed that SCF stimulation induced the activation of Akt and STAT3 in migrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…Glyceryl trinitrate inhibits JAK2 through s-nitrosylation to suppress IL-6-induced migration and invasion in TNBC cells. Additionally, glyceryl trinitrate infusion decreases lung metastatic lesions in a TNBC syngeneic mouse model ( 147 ). Pentadecanoic acid suppresses the CSC subpopulation through inhibition of IL-6/JAK/STAT3 signaling and increases apoptosis in ER+ breast cancer cell line; however, the exact mechanism remains unknown ( 148 ).…”
Section: Current Therapeutic Applications Of Il-6 Signaling In Breast...mentioning
confidence: 99%
“…Invasion was also significantly lower in CM from unirradiated spheroids co-cultured with macrophages. Previous studies have shown that neutralization of IL-6 reduces invasiveness of 4T1 cells and that macrophage-derived IL-6 contributes to tumor cell migratory ability 37,38 . However, we are the first to show the dependence of 4T1 invasiveness on IL-6 secreted from stromal-macrophage interactions.…”
Section: Resultsmentioning
confidence: 99%